Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1212/wnl.46.5.1347
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese boy with myalgia and cramps has a novel in‐frame deletion of the dystrophin gene

Abstract: We report a Japanese Becker muscular dystrophy (BMD) patient with occasional myalgia and cramps during normal activity that developed at the age of 28 months. His family history was negative for neuromuscular diseases. Muscle biopsy analyses, including dystrophin immunostaining, disclosed no clinically relevant findings. The diagnosis of BMD was initially made at the age of 10 years, when indications of persistent high serum levels of CK prompted us to screen deletions in the dystrophin gene by amplification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…17 Deletions removing only the first part of the central rod domain have been found in asymptomatic individuals, in persons with elevated serum creatine kinase levels, and in patients suffering from muscle cramps upon exercise. 2,24,32 In-frame deletions within exons 2-8 (the actin-binding domain) cause severe BMD, whereas deletions in the major hotspot generally cause typical BMD. 6,49 It was recently reported that deletions that include the third hinge region are generally associated with milder phenotypes than those that do not involve this hinge region.…”
Section: Relation Between Size and Location Of Mutations And Phenotypementioning
confidence: 99%
“…17 Deletions removing only the first part of the central rod domain have been found in asymptomatic individuals, in persons with elevated serum creatine kinase levels, and in patients suffering from muscle cramps upon exercise. 2,24,32 In-frame deletions within exons 2-8 (the actin-binding domain) cause severe BMD, whereas deletions in the major hotspot generally cause typical BMD. 6,49 It was recently reported that deletions that include the third hinge region are generally associated with milder phenotypes than those that do not involve this hinge region.…”
Section: Relation Between Size and Location Of Mutations And Phenotypementioning
confidence: 99%
“…Even though the central rod domain and hinge regions that connect these essential domains are thought to be redundant, some parts are probably more important than others, and consequently, not all internally deleted dystrophins will be equally functional. In fact, in-frame deletions in the proximal regions of the central rod domain (exons 20-40) are generally milder than those in the distal part (exons 40-55) [Aartsma-Rus et al, 2006b;Angelini et al, 1994;Beggs et al, 1991;Gospe et al, 1989;Ishigaki et al, 1996]. In addition, it has been reported that the presence or absence of the hinge regions may influence functionality [Carsana et al, 2005;Yokota et al, 2007].…”
Section: Overall Applicabilitymentioning
confidence: 99%
“…DNA analysis revealed a deletion of exons 13-18 in the dystrophin gene. 3 In our family all the symptomatic patients had calf hypertrophy but females as well as males seemed to be affected. Three females (I,2, II,1, II,3) presented with cramps after exercise, nocturnal cramps, calf hypertrophy, and raised serum CK.…”
Section: Discussionmentioning
confidence: 58%
“…[1][2][3][4][5][6] FigarellaBranger et al 2 found five males with exercise intolerance and abnormal immunohistochemistry. DNA analysis revealed a deletion in the dystrophin gene in two of these patients, affecting the proximal part of the rod domain in one and the distal part of this domain (exons 45-52) in the other.…”
mentioning
confidence: 99%